Financial Exploitation: A Qualitative Analysis from Türkiye - Mustafa Can Samirkas; Meryem Samirkas Komsu; Ufuk Cem Komsu; Samet Evci (International Journal of Financial Studies)
Elderly individuals who need the support of others may be subjected to abuse in managing their budgets and financial decisions. This situation is explained as financial exploitation, which is a subtype of elder abuse. The main purpose of this study is to evaluate the participants’ financial decision-making skills and their exposure to financial exploitation. In this study, which was designed according to qualitative research design, data were collected through semi-structured interview forms. The collected data were analyzed by creating themes according to the general framework coding method. The results of the study reveal that the participants receive help from their children in financial decision-making and that their children generally manage their budgets. Moreover, although the income levels of the participants are generally quite low, it is seen that they are exposed to financial exploitation by their families and people in their immediate vicinity.